Incidence, Time Trends, and Predictors of Intracranial Hemorrhage During Long‐Term Follow‐up After Acute Myocardial Infarction - Graipe, Anna (J Am Heart Assoc, 2015)
BACKGROUND: To address the lack of knowledge regarding the long‐term risk of intracranial hemorrhage (ICH) after acute myocardial infarction (AMI), the aims of this study were to: (1) investigate the incidence, time trends, and predictors of ICH in a large population within 1 year of discharge after AMI; (2) investigate the comparative 1‐year risk of ICH in AMI patients and a reference group; and (3) study the impact of previous ischemic stroke on ICH risk in patients treated with various antithrombotic therapies. METHODS AND RESULTS: Data about patients whose first AMI occurred between 1998 and 2010 were collected from the Swedish Register of Information and Knowledge about Swedish Heart‐Intensive‐Care Admissions (RIKS‐HIA). Patients with an ICH after discharge were identified in the National Patient Register. Risk was compared against a matched reference population. Of 187 386 patients, 590 had an ICH within 1 year. The 1‐year cumulative incidence (0.35%) was approximately twice that of the reference group, and it did not change significantly over time. Advanced age, previous ischemic or hemorrhagic stroke, and reduced glomerular filtration rate were associated with increased ICH risk, whereas female sex was associated with a decreased risk. Previous ischemic stroke did not increase risk of ICH associated with single or dual antiplatelet therapy, but increased risk with anticoagulant therapy. CONCLUSION: The 1‐year incidence of ICH after AMI remained stable, at ≈0.35%, over the study period. Advanced age, decreased renal function, and previous ischemic or hemorrhagic stroke are predictive of increased ICH risk.